2016
DOI: 10.1177/0963662515615087
|View full text |Cite
|
Sign up to set email alerts
|

The influence of weight-of-evidence strategies on audience perceptions of (un)certainty when media cover contested science

Abstract: Controversy in science news accounts attracts audiences and draws attention to important science issues. But sometimes covering multiple sides of a science issue does the audience a disservice. Counterbalancing a truth claim backed by strong scientific support with a poorly backed argument can unnecessarily heighten audience perceptions of uncertainty. At the same time, journalistic norms often constrain reporters to "get both sides of the story" even when there is little debate in the scientific community abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…An alternative to falsely balanced discussions, which potentially can alter the environment in favour of evidence-based perspectives, is weight-of-evidence reporting ( Dunwoody, 2005 ; Kohl et al, 2016 ). A weight-of-evidence strategy ‘calls on journalists not to determine what’s true, but instead to find out where the bulk of evidence and expert thought lies on the truth continuum and then communicate that to the audiences’ ( Dunwoody, 2005, p. 90 ).…”
Section: Weight-of-evidence Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…An alternative to falsely balanced discussions, which potentially can alter the environment in favour of evidence-based perspectives, is weight-of-evidence reporting ( Dunwoody, 2005 ; Kohl et al, 2016 ). A weight-of-evidence strategy ‘calls on journalists not to determine what’s true, but instead to find out where the bulk of evidence and expert thought lies on the truth continuum and then communicate that to the audiences’ ( Dunwoody, 2005, p. 90 ).…”
Section: Weight-of-evidence Strategiesmentioning
confidence: 99%
“…A weight-of-evidence strategy ‘calls on journalists not to determine what’s true, but instead to find out where the bulk of evidence and expert thought lies on the truth continuum and then communicate that to the audiences’ ( Dunwoody, 2005, p. 90 ). Thus, weight-of-evidence strategies neither overestimate positions that are backed up with little evidence, nor do they neglect the existence of contrasting positions ( Kohl et al, 2016 ). Instead, weight-of-evidence strategies provide each position in a public discussion with a weight corresponding to the amount of evidence that supports the position.…”
Section: Weight-of-evidence Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown that people's perceptions of scientific consensus-the extent to which scientists agree on a scientific issue-predict and influence their beliefs about the issue (Cook & Lewandowsky, 2016;Ding, Maibach, Zhao, Roser-Renouf, & Leiserowitz, 2011;Dixon & Clarke, 2013;Dunwoody & Kohl, 2017;Kohl et al, 2016;Lewandowsky, Gignac, & Vaughan, 2013;McCright, Dunlap, & Xiao, 2013;van der Linden, Clarke, & Maibach, 2015;. That is to say, those who estimate greater consensus among scientists on the existence of a scientific phenomenon (e.g., anthropogenic climate change) or causality (e.g., vaccine-autism link) are more likely to accept and be certain about the scientific phenomenon or causality.…”
Section: Introductionmentioning
confidence: 99%